1965
DOI: 10.1042/bj0940751
|View full text |Cite
|
Sign up to set email alerts
|

Liver Lipids of Choline-Deficient Rats

Abstract: 1. Four-week-old male and female rats were given choline-deficient diets for 2 weeks. Deficient animals gained nearly as much weight as normal controls of the same sex. 2. The amounts of triglyceride and esterified cholesterol in liver lipids were increased threefold or more by the deficiency. The amounts of the major phosphatides and of unesterified cholesterol were unaffected. 3. In males, deficiency significantly increased the proportion of stearic acid in triglycerides, and, in females, the proportion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

1966
1966
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…Although variations in means for the various groups were found, the differences were not significant. The levels of the various lipid fractions found were in general agreement with previously published results (Cook, 1958;Campbell and Kosterlitz, 1947 ; Tinoco et al, 1965).…”
Section: Chemicalsupporting
confidence: 82%
“…Although variations in means for the various groups were found, the differences were not significant. The levels of the various lipid fractions found were in general agreement with previously published results (Cook, 1958;Campbell and Kosterlitz, 1947 ; Tinoco et al, 1965).…”
Section: Chemicalsupporting
confidence: 82%
“…The lower ratio of total radioactivity of serum TG to that of liver TG in the later phase of the experiment (Table 5) is also consistent with the possibility of decreased secretion of lipid from the liver into the blood . Some of the effects of pyridoxine deficiency on liver and serum lipid compositions are similar to those of choline deficiency (39,40), but the reason for the decreased level of PC in pyridoxine-deficient liver is not known. Recently, Abe et al (41) reported that starvation for 4 days decreased the level of PC and inversely increased the PE content of rat liver.…”
Section: Discussionmentioning
confidence: 83%
“…Other evidence that this pathway for lecithin synthesis may be important in the feinale rat has been obtained in rats fed diets low i l l ~nethyl groups and deficient in choline (13). Under these conditions, serum phospholipids were depressed, and sex differences in their fatty acid co~nposition were abolished.…”
Section: Discussionmentioning
confidence: 94%
“…Our interest in these sex differences in plasma cholesterol and phospholipid fatty acids was stilnulated when it was observed that the sex differences in stearic acid/palmitic acid ratios disappeared in choline-deficient male and fenlale rats (13). We therefore conducted experiments to learn whether estrogen or androgen was responsible for the observed differences, and what specific changes in the proportions of fatty acids of the subclasses of plasma phospholipids may have been induced by the hormones.…”
Section: Introductionmentioning
confidence: 96%